2017
DOI: 10.1242/jeb.144253
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin induces clock gene expression in the liver of goldfish in vitro via protein kinase C and protein kinase A pathways

Abstract: The liver is the most important link between the circadian system and metabolism. As a food-entrainable oscillator, the hepatic clock needs to be entrained by food-related signals. The objective of the present study was to investigate the possible role of ghrelin (an orexigenic peptide mainly synthesized in the gastrointestinal tract) as an endogenous synchronizer of the liver oscillator in teleosts. To achieve this aim, we first examined the presence of ghrelin receptors in the liver of goldfish. Then, the gh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…The existence of a rhythmic expression of all the components of the ghrelinergic system (ghrelin, GOAT and its main receptor) indicates that this system may be acting as an output of the circadian system in goldfish. Besides, the modulation of clock genes expression by ghrelin in goldfish tissues both in vivo [ 12 ] and in vitro [ 14 ] points to the ghrelinergic system as an input signal for the circadian system in fish.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of a rhythmic expression of all the components of the ghrelinergic system (ghrelin, GOAT and its main receptor) indicates that this system may be acting as an output of the circadian system in goldfish. Besides, the modulation of clock genes expression by ghrelin in goldfish tissues both in vivo [ 12 ] and in vitro [ 14 ] points to the ghrelinergic system as an input signal for the circadian system in fish.…”
Section: Resultsmentioning
confidence: 99%
“…This includes a role in a wide variety of physiological processes of all vertebrates, including fish, such as stimulation of growth hormone release from the pituitary, stimulation of food intake, carbohydrate utilization and adiposity and regulation of insulin secretion, among others [ 7 11 ]. In the last decade, ghrelin has also been involved in the circadian system of both mammals and fish, where it might act as both an input [ 12 14 ] and an output signal [ 15 ]. Although acylated ghrelin (acyl-GRL) is typically considered as the active form of the hormone, studies have recently shown that deacylated ghrelin (desacyl-GRL) also has some biological functions in vertebrates [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Just like other crucial functions, such as feeding regulation, temporal homeostasis in the liver is probably regulated by multiple redundant signals. Specifically in goldfish, the orexigenic peptides orexin [26] and ghrelin [27,48], whose levels increase during fasting [49], can modulate the food anticipatory activity (FAA), which is the primary output of the food-entrainable oscillator (FEO) [26,27]. Unlike orexin and ghrelin, insulin levels increase directly in response to feeding [28,29]; thus, a stronger direct impact as a feeding input could be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike orexin and ghrelin, insulin levels increase directly in response to feeding [28,29]; thus, a stronger direct impact as a feeding input could be expected. Furthermore, several hormones apart from insulin directly affect clock gene expression in the fish liver, including ghrelin and also glucocorticoids, which will be further discussed [48,50]. Even more feeding-related signals have been implicated in liver clock entrainment in mammals, such as IGF-1 and oxyntomodulin (a hormone released by gastric filling), via induction of per1 and per2 [38,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation